2017
DOI: 10.1037/sah0000062
|View full text |Cite
|
Sign up to set email alerts
|

The experience of weight stigma among gym members with overweight and obesity.

Abstract: Persons with obesity face frequent instances of weight-related victimization and discrimination. To date, however, no research has assessed weight stigma within fitness facilities among a sample of gym members with overweight and obesity. Given the role of exercise in mitigating the health risks of obesity, it is vital to assess the presence of weight stigma within exercise facilities. We therefore assessed weight stigma within fitness facilities, factors affecting motivation to exercise, and factors that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 70 publications
1
60
0
Order By: Relevance
“…Six studies have examined associations between WBI and mental HRQOL using the Mental Component Summary Score of the SF‐12 or SF‐36 . Across these studies, WBI was significantly and negatively associated with mental domains of quality of life, and these findings remained consistent for both the WBIS and WSSQ.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Six studies have examined associations between WBI and mental HRQOL using the Mental Component Summary Score of the SF‐12 or SF‐36 . Across these studies, WBI was significantly and negatively associated with mental domains of quality of life, and these findings remained consistent for both the WBIS and WSSQ.…”
Section: Resultsmentioning
confidence: 93%
“…Seven studies consistently showed significant associations between WBIS scores and physical HRQOL . For example, Latner et al .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations